Implementation of a thermostatic suit for thermal comfort control in order to improve performance on the job - Meléndres Medina, Edison (2017)
The present research explains the impact of thermal comfort on the welfare, health and performance of workers in San Juan political tenure, considering that the current environmental conditions are too cold, workers wear uniforms that do not allow them to maintain A suitable temperature, accentuating the physical and psychological discomforts characteristic of the low temperatures that makes the worker stay in a permanent thermal stress, this affects not only the individual but the performance in the tasks assigned; Under this scenario was designed and implemented the use of a thermo-adjustable suit that allows to maintain optimum conditions of temperature adaptable to each individual using electronic devices, thus obtaining positive results from the users that allows us to understand that the security objectives have been met Industrial, occupational health and risk prevention, contributing authentically to the development of work activities, based on the human being's well-being and development.